From Identity Politics to Internalized Oppression: Navigating Positionality in Disability Research - Katzman, Erika (Revista Mundaú, 2023)
The primacy of experiential knowledge is an undisputed foundation of disability activism and scholarship. Identity politics and intersectionality draw attention to the limited range of voices, interests and experiences represented in first wave disability organizing. Meanwhile, an emergent second wave urges a shift in focus from disabled identity to the interconnected systems of domination and exploitation that shape our embodied experience. Through critically reflexive interrogation of the author’s amorphous positionality, as a neurodivergent but otherwise non-disabled care worker turned health professional and disability scholar, this paper explores the relationship between disabled identity, membership in disability culture and experiential knowledge. A relational understanding of disability opens space to consider the legitimacy and value of disability-adjacent identities and perspectives. Limitations of participatory methodological approaches are considered and the emancipatory potential of reflexive ethnographic methodology is discussed.